Diego Granado Maldonado - Allard, Jeanne (Petits Propos Culinaires, 2024)
One of the best known of the very early Spanish cookery books is that by Diego Granado. So far as we know, it has always been accepted, both inside and outside Spain, as a work of a truly Spanish nature and of some originality. Jeanne Allard has investigated its origins, with surprising results.